Assessing Head Injury of Civilian UAV Safety Systems: A Test Apparatus and Spherical Shell Example - Eric J. Hettel; Hossein Eslamiat; Mohammed Aleemuddin; Mohsen Farajijalal (IEEE Access)
In recent years, flying vehicles have become an innovative way to transfer parcels efficiently over a short distance. Existing airspace regulations are slow to adapt to the anticipated rise in aircraft traffic resulting from this development. This is because the increase in unmanned aerial vehicles (UAVs) comes with an increased risk of personal injuries from faulty drones carrying a payload. Many national regulatory agencies, such as the FAA, rely on the Abbreviated Injury Scale (AIS) to determine the weight threshold of a UAV by evaluating the impact energy and correlating it to the severity of a potential injury. This research paper presents a test apparatus to investigate the effect of different safety systems on AIS.As an example, a passive safety system in the form of a geodesic shell is used to investigate the change in impact acceleration and therefore, the head injury sustained. The spherical shell is designed as a geodesic sphere. Its struts are carbon fiber reinforced polymer (CFRP) rods and connectors made from a flexible filament, TPU-95A. The apparatus enables droppings of the geodesic shell from a height of 4.48 meters,varying the payload weight in two weight classes between 2.5 lb to 5 lb attached to the drone. The impact acceleration is recorded, and the impact velocity is calculated using slow-motion video. The Head Injury Criterion (HIC) scale and the Abbreviated Injury Scale (AIS) are used to measure the predicted head injury level. The test apparatus designed establishes a standard of testing for other safety systems, in addition to geodesic shells like airbags, to be tested for their efficacy in reducing the head injury level sustained.